Complex Regional Pain Syndrome Associated with Herpes Zoster: A Case Report - Pınar ÖZTOP; Sacide Nur SARAÇGİL COŞAR and Oya ÜMİT YEMİŞCİ and; a Sedef VAROL ÜRE2 (Archives of Rheumatology, 2011)
Complex regional pain syndrome (CRPS) is a clinical syndrome characterized by pain, tenderness, dystrophic skin changes, swelling, stiffness in joints, and vascular instability. The pathogenesis of CRPS is not completely understood, and no single hypothesis proposed to date has explained all the features of this disorder. However, several predisposing factors have been identified. This report describes an unusual cause of CRPS. Although CRPS following herpes zoster is clinically well recognized, only a few documented cases have been reported to date. Here, we present a case of 64-year-old woman with characteristic signs and symptoms of CRPS in the right hand that appeared four weeks after she had a typical herpes zoster infection involving the right C7-C8 dermatomes. Early diagnosis and treatment with medical and physical therapy achieved a progressive improvement of the disease within a brief period of time. In this report, we aim to draw attention to CRPS which can occur as a result of very different conditions. Recognition and knowledge of CRPS are important since a delay in proper diagnosis and treatment may have a negative effect on a patient’s prognosis.